The frame of fixed stars in Relational Mechanics - Ferraro, Rafael (2016)
Relational mechanics is a gauge theory of classical mechanics whose laws do not govern the motion of individual particles but the evolution of the distances between particles. Its formulation gives a satisfactory answer to Leibniz’s and Mach’s criticisms of Newton’s mechanics: relational mechanics does not rely on the idea of an absolute space. When describing the behavior of small subsystems with respect to the so called “fixed stars”, relational mechanics basically agrees with Newtonian mechanics. However, those subsystems having huge angular momentum will deviate from the Newtonian behavior if they are described in the frame of fixed stars. Such subsystems naturally belong to the field of astronomy; they can be used to test the relational theory.